HEAT EVOLUTION OF ETHANOL FERMENTATION USING SACCHAROMYCES CEREVISIAE CSI-1 - STANLEY, ANTHONY NYOEL (Universiti Malaysia Sarawak, (UNIMAS), 2018)
The exothermic reaction during the ethanol fermentation has been a major problem in the industry as high cost was required for heat control especially in tropical countries. Hence, the ethanol fermentation was studied through the heat evolution using Saccharomyces cerevisiae CSI-1 yeast and also the relationship between small scale and pilot scale fermentations. The small-scale fermentation was started at room temperature in a 3-L bioreactor and using 200 g/L glucose with 5g/L yeast extract as fermentation medium. Temperature, Optical density and pH were monitored and recorded during the fermentation. The fermentation gave a yield of 0.511 g glucose/g ethanol with final ethanol concentration of 102.26 g/L after 26 hours. The same parameters were observed for the pilot scale fermentation in a 100 L open Stirred Tank Reactor (STR) where the yield is 0.508 g glucose/g ethanol and final ethanol concentration of 101.655 g/L after 120 hours. This showed that the small-scale and pilot scale has the same amount of product produced and that they differed in terms of fermentation time. Lastly, simulation on the fermentation using SuperPro software was conducted based on the data obtained from the pilot scale fermentation where the simulated fermentation time was reduced to 78 hours.